What explains Germany's rebounding export market share? - Stephan Danninger; Fred Joutz (Center for Economic Studies and ifo Institute (CESifo), 2007)
Germany's export market share increased since 2000, while most industrial countries experienced declines. This study explores four explanations and evaluates their empirical contributions: (i) improved cost competitiveness, (ii) ties to fast growing trading partners, (iii) increased demand for capital goods, and (iv) regionalized production of goods (e.g. off-shoring). An export model is estimated covering the period 1993 2005. The dominant factor explaining the increase in market share are trade relationships with fast growing countries. Regionalized production in the export sector also played a part. Improved cost competitiveness had a comparatively smaller impact. There is no conclusive evidence of increased demand for capital goods.
Keywords: C22; F41; 330; Auslandsmarkt; Export; Erfolgsfaktor; Deutschland